Break the Limits: INGOs Limitation and Learning from Amnesty International - Anindita, Vinesha Anindita (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
Civil society as the beginning of the notions of INGOs gives a holistic view to analyze the problem and the limit of International non-governmental organizations (INGOs) itself. Critics that arises regarding the limit of INGOs is the lack of independence of INGOs that is questionable about the possibility of the dependence of funds even from individual actor to government fund. It can reduce the roles and the functions of INGOs to act objectively. Another critic for INGOs is a complex matter for international organizations in general about the lack of accountability. So many questions about how do INGOs can be more accountable or whom INGOs should be accountable. This paper argues that accountability should not just for the donors or the government but also stakeholder/grassroots. But, the limit of INGOs can be answered by Amnesty International which is a contradiction example of international organizations that is not affected by the limit of INGO.